(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Amavata is one of the challenging diseases for the physicians due to its chronicity, incurability, complications and morbidity. It is decided to evaluate certain Ayurvedic management for a series of patients of rheumatoid arthritis which could be safe, effective, cheap, and easily available. Methodology: Total 56 patients of RA (Amavata) fulfilling the inclusion criteria and having symptoms of RA were enrolled for clinical trial from OPD & IPD of department of Kayachikitsa, SS Hospital, IMS, BHU, Varanasi. Patients were treated in four different groups- Group A- 18 clinically diagnosed and registered patients of Amavata were treated by- Rasnasaptak Kwath- 40ml BD with lukewarm water. Group B: 16 clinically diagnosed and registered patients of Amavata were treated by Vaitarana Vasti for 2 times at interval of 15 days in the format of Yoga Vasti with Anuvasana of Saindhavadi Talia. Group C: 5 clinically diagnosed and registered patients of Amavata were treated by- Rasnasaptak Kwath and Vaitarana Vasti. Group D: 17 clinically diagnosed and registered patients of Amavata were treated by- Leflunomide 10mg OD Results: After the trial, treatment given for the clinical study, we got Vata-Kapha trait appears to be more vulnerable for Amavata disease. Overall effect of trial suggests that group C provided better improvement in comparison to group A, B and D in maximum objective and subjective criteria. Discussion: The study concludes that, planned trial drugs and procedure are effective in terms of reduction of symptomatology of Amavata (RA) as compared to standard treatment group.